THEORETICAL FOUNDATIONS OF THE BANKING SERVICES MARKET IN AGRICULTURE - Xidirovich, Hamrayev Fayzulla; Fayozbek, Fayzullayev (Research Focus International Scientific Journal, 2026)
This article discusses the theoretical foundations of banking services and analyzes banking services and operations. The article develops scientific and practical recommendations based on analysis.